Into the wild: Survival, movement patterns, and weight changes in captive Ethiopian hedgehogs, Paraechinus aethiopicus following their release. (November 2018) - Abu Baker, Mohammad A.; Villamil, Luis Alberto; Reeve, Nigel; Karanassos, Christina; Mahtab, Hazim; Yamaguchi, Nobuyuki
Abstract: The survival, movement, and weight changes of 24 Ethiopian hedgehogs ( Paraechinus aethiopicus ) were monitored following their release from captivity. A total of 13 females and 11 males were released and radio-tracked for 2–4 weeks. 95% were alive after two weeks, and at least 54% were known to have survived throughout the study the remaining include 7 animals whose signals were lost after 3–24 days and 4 deaths after 3–24 days). The average daily distance travelled and distance between shelters ranged between 131.4–426.7 m and 103–1102 m, respectively. Distances were larger during the first week, for females than males, and for captive-born than wild-born. Twenty-one of the released hedgehogs showed significant weight loss during the monitoring periods; changes were between −25.0 and + 6.7 percent of starting body weight. Rates of weight loss were highest during the first week for both sexes and similar for wild-born and captive-born animals, but significantly greater for females. Stable bodyweights comparable to those of wild conspecifics were achieved after 23 days. This is the first study to evaluate the response of captive Ethiopian hedgehogs to release into the wild, which can inform future translocation and reintroduction efforts. Highlights: The study tested the feasibility of releasing captive animals into the wild, and was done in an arid area in Qatar. In Arabia, wildlife loss is accelerating due to land use changes, such as agricultural expansion and large-scale development. Little is known about the study species, which is the main insectivore in the ecosystem. This is the first study demonstrating the feasibility of releasing captive-born hedgehogs into the wild. It also provides data on their movement patterns and body weight changes.